Personalized and Precision Medicine 2022 - Caminade, Anne-Marie (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint, guest edited by Anne-Marie Caminade, gives an impressionist overview of the current state of the art about "Personalized and Precision Medicine". Twenty contributions illustrate the diversity of the topic, including new approaches about cancers, neurodegenerative diseases, infectious diseases, lungs obstruction, skeletal diseases, intestinal microbiomes, new tools such as ultra-high-frequency ultrasound or non-oncological radiotherapy, and a new class of drugs (dendrimers). This reprint is an illustration of the present and future impact of Personalized and Precision Medicine on all the therapeutic domains.